Los centros de internamiento de extranjeros (CIE) en España: función, perfiles de la población internada y posibilidades de asistencia social en su interior (2021)
In the last two decades, there has been a tightening of immigration policies in the European Union, which has increased after the last economic crisis in 2008. Currently, the control of migratory flows focuses on three objectives: limiting the entry of foreigners, hindering their administrative regularization, and facilitating their expulsion from European territory. Spain, due to its geopolitical peculiarities, as it is the gateway to Europe from Africa and Latin America, presents an important activity in terms of detentions and expulsions, and has several detention centers for foreigners distributed throughout the country. Through qualitative empirical research, this article identifies the main challenges faced by social workers in their professional performance in the Aluche Internment Center. To that end, a bibliographic and documentary review and a legal-normative analysis were carried out. Likewise, reflections on some of the most relevant needs and aspects related to the interned population as well as on how the structure and operation of the center limit the professional work are presented.